2018
DOI: 10.1111/ijcs.12466
|View full text |Cite
|
Sign up to set email alerts
|

Is buying counterfeit sinful? Investigation of consumers’ attitudes and purchase intentions of counterfeit products in a Muslim country

Abstract: The study investigates the effect of individuals’ ethics (i.e., idealism and relativism), religiosity (i.e., fear of divine punishment, interest in religion and practices, and beliefs in religion), and attitudes toward counterfeits (i.e., economic benefits and hedonic benefits) on purchase intentions of counterfeit products. Data were collected in Tunisia, a Muslim country showing a mixture of modern and conservative values. The analysis of variance on the data, collected among 217 participants, shows that rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 97 publications
(210 reference statements)
1
29
0
Order By: Relevance
“…The initial scale comprised 35 items distributed on 4 dimensions, consistent with the ethical attitude model towards the use of information technology (IT). For the needs factor associated with the cognitive component, in Dimension 1, 17 items were developed, of which items CN1, CN2, CN7 were adapted after Sondhi [77], the item CN5 after Gregory and Noto [78], the CN6 item after Pérez-Rodríguez et al [79], items CN9, CN10, CN11, CN12, CN13, CN14, CN15, CN16, CN17 after Hashim and Hassan [80], and items CN3, CN4, CN8 are original. For the constraints factor associated with the cognitive component, within dimension 2, 6 items were developed, of which all items CC1, CC2, CC3, CC4, CC5, and CC6 are original.…”
Section: The Survey Instrumentmentioning
confidence: 99%
“…The initial scale comprised 35 items distributed on 4 dimensions, consistent with the ethical attitude model towards the use of information technology (IT). For the needs factor associated with the cognitive component, in Dimension 1, 17 items were developed, of which items CN1, CN2, CN7 were adapted after Sondhi [77], the item CN5 after Gregory and Noto [78], the CN6 item after Pérez-Rodríguez et al [79], items CN9, CN10, CN11, CN12, CN13, CN14, CN15, CN16, CN17 after Hashim and Hassan [80], and items CN3, CN4, CN8 are original. For the constraints factor associated with the cognitive component, within dimension 2, 6 items were developed, of which all items CC1, CC2, CC3, CC4, CC5, and CC6 are original.…”
Section: The Survey Instrumentmentioning
confidence: 99%
“…The study of counterfeit luxury goods consumption has received much attention from scholars, researchers, and policymakers during the past decades because it intensifies the tension of revenue loss to companies and ethical concerns to societies (Souiden et al, 2018). This study provides an insight regarding the factors affecting consumers' purchas intention for counterfeit luxury goods from the perspective of Bangladesh.…”
Section: Managerial Implicationmentioning
confidence: 99%
“…In particular, the role of attitude is the most influential among the three variables of TPB, indicating the critical role of individuals' attitudes towards counterfeit outdoor products in purchase intention. Many studies have also found similar results that when individuals have a more favourable and positive attitude towards counterfeits, they are more likely to make a purchase of counterfeits (Sharma and Chan, 2017;Souiden et al, 2018).…”
Section: Discussionmentioning
confidence: 65%